A comparative analysis of existing models and a new pushover analysis model of reinforced concrete sections. (1st January 2023) - Kimeze, Henry; Kyakula, Michael
Highlights: Comparative analysis of push-over analysis models. Existing models ignore cracking. A new model that considers cracking is introduced. Accuracy of deformations during pushover analysis of reinforced concrete structures. New pushover analysis model compared with experimental results. Abstract: Pushover analysis is mainly carried out using the concentrated plasticity model whereby when a point reaches yield, a hinge is placed at that point. The other is the yielded block spread plasticity model, whereby when a point reaches yield, an elastic sub-element of the beam is replaced by a yielded sub-element having a reduced cross-section and second moment of area. Both of these models ignore cracking. This study aims at giving an insight into the effects of considering cracking during modelling on the accuracy of estimating deformations in reinforced concrete (RC) structures during pushover analysis by proposing a spread cracking and yielding block model. The proposed model introduces a cracked sub-element to account for the gradual spread of cracking in the beam. A single-storey RC frame is used because it doesn't pose the challenge of lateral load distribution. A comparison between the proposed model and the existing models shows an increment in the accuracy of the rotational, displacement, moment and lateral load capacities of 63.64%, 56.86%, 64.33% and 55.56% respectively. Experimental results show that all theoretical models underestimate the ultimate floor displacements and lateral load capacities. The proposed model, however, has better accuracy on both fronts than both existing theoretical models.